Engineering Secure Software and Systems 8th International Symposium, ESSoS 2016, London, UK, April 6-8, 2016. Proceedings - Caballero, Juan; Bodden, Eric; Athanasopoulos, Elias (Security and Cryptology, 2016)
This book constitutes the refereed proceedings of the 8th International Symposium on Engineering Secure Software and Systems, ESSoS 2016, held in London, UK, in April 2016. The 13 full papers presented together with 3 short papers and 1 invited talk were carefully reviewed and selected from 50 submissions. The goal of this symposium, is to bring together researchers and practitioners to advance the states of the art and practice in secure software engineering. The presentations and associated publications at ESSoS 2016 contribute to this goal in several directions: First, by improving methodologies for secure software engineering (such as flow analysis and policy compliance). Second, with results for the detection and analysis of software vulnerabilities and the attacks they enable. Finally, for securing software for specific application domains (such as mobile devices and access control).